Functional Outcome of Hybrid External Fixator in Tibial Pilon Fractures - Ranjeet, Niraj; Sapkota, Krishna; Thapa, Pabin; Onta, Pratyenta Raj; Thapa, Upendra Jung; Wahegaonkar, Krishna (Nepal Journal of Medical Sciences, 2022)
Introduction: Tibial pilon fractures are difficult fractures mostly secondary to high-energy trauma. There are various options to treat these fractures, but the priority is always an anatomic reduction and articular congruity with good soft tissue handling. The aim of the study was to analyze the functional outcome of tibial pilon fractures managed with a hybrid external fixator as definitive management. Methods: We evaluated 28 patients with tibial pilon fractures with a mean age of 34.8 years. All patients who fulfilled the inclusion criteria were taken to the operating room for debridement and application of a hybrid external fixator. Results: The most common mechanism of injury was road traffic accidents and most of our patients had comminuted fractures. The fibula was fractured in 23 (82.14%) of our patients. The fractures united on an average of 15.28 weeks. Based on the Ovadia & Beals objective scoring system 75% of our patients scored excellent or good on objective scoring and subjective scoring 82.14% of our patients scored excellent or good. We had 12 cases of pin tract infection, 2 cases of delayed union, and 2 cases of malunion but no incidence of non-union, osteomyelitis, or septic arthritis. Eight of our patients had ankle joint stiffness. Conclusion: Hybrid external fixator is an effective method of treatment for tibial pilon fractures with comparable union rate and complications to other modalities.